Preservation Of Old Buildings And Its Importance For City Landscaping And Sustainability - Valentim Neto, Manoel Vicente (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective - Analyze the importance of preserving old buildings for urban landscaping, highlighting their contributions to collective memory, the city’s aesthetic harmony, and sustainable development. Methodology - The methodology used in this study seeks information on the relationships between built space, natural landscape, cultural landscape and landscape practices, through exploratory research and bibliographic review, also using secondary sources of information. Originality/Relevance - The scarcity of financial resources, which is normally used as justification for the clumsy application of urban development to the detriment of historical preservation and landscape, makes it necessary to preserve old properties to maintain the city’s landscape memory. Results - Preservation is essential to promote more balanced cities, with a focus on sustainability, cultural tourism, and heritage education. Theoretical/methodological contributions – The importance of relationships between built space, natural landscape, cultural landscape and landscaping practices in the preservation of old properties. Social and environmental contributions – The indispensable practice to guarantee the maintenance of the identity of cities, the relationships between built space, natural landscape, cultural landscape and landscaping practices, the preservation of history through ancient architecture and urban development in a responsible and inclusive manner.